2021
DOI: 10.1002/ags3.12489
|View full text |Cite
|
Sign up to set email alerts
|

The new prognostic score for unresectable or recurrent gastric cancer treated with nivolumab: A multi‐institutional cohort study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…More than half of the studies were reported from the Far East (n = 15) (Ichiki et al, 2019;Jiang et al, 2020;Kitadai et al, 2020;Takada et al, 2020;Ke et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Pu et al, 2021;Sato et al, 2021;Tokuyama et al, 2021;Chen et al, 2022;Kim et al, 2022;Li et al, 2022;Wu et al, 2022;Zhang et al, 2022), followed by Europe (n = 12) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Svaton et al, 2018;Cantini et al, 2020;Awada et al, 2021;Onn et al, 2021;Ruiz-Bañobre et al, 2021;Stares et al, 2021;Assié et al, 2022;Schneider et al, 2022;Stares et al, 2022). A 3.5 gr/dL albumin cut-off was most frequently used in the included studies (n = 20) (Dercle et al, 2016;Bigot et al, 2017;Mezquita et al, 2018;Formica et al, 2020;Jiang et al, 2020;Kitadai et al, 2020;Lee et al, 2020;Takada et al, 2020;Awada et al, 2021;Brown et al, 2021;Khaki et al, 2021;Morimoto et al, 2021;Ng et al, 2021;Onn et al, 2021;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…It is regularly assessed during the treatment of these patients; nevertheless, little is known about the impact of the nutritional status on the efficacy of immunotherapy. Moreover, only a few small studies have evaluated nutritional indexes in standard chemotherapy-treated mGOJ/GC patients, with these indexes being mostly based on inflammation parameters (i.e., CRP), all of them in pan-Asian cohorts (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…It combines the serum albumin, a proxy of nutritional status and a marker of stem-cell differentiation and apoptosis (25)(26)(27)(28), and the total lymphocyte count, that is known to be positively associated with response to chemotherapy and survival in mGOJ/GC (29,30). Hypoalbuminemia especially is commonly studied alone (21) or in combination with other lab values as neutrophil-to-lymphocyte ratio, CRP (31), serum lactate dehydrogenase (32) or total cholesterol level (33) as a negative predictor of treatment outcome in mGOJ/GC patients treated with anti-PD-1 agents. In our work, albumin level confirmed its prognostic value in univariate but not in multivariate analysis, while PNI retained significance value at P<0.05.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other already established prognostic tools, the VIOLA score is favourable for several reasons. Major contributors to low feasibility in everyday practice of other scores are (i) the need for information that is not available at initial diagnosis, such as specific treatment information 22 , 23 , 26 , 27 ; (ii) the need for information that needs to be evaluated solely to calculate the score 28 , 29 , 30 ; (iii) complicated calculations to get appropriate score results. 31 Another important issue of existing scores is the fact that known key prognostic factors such as age and sex are often not included and, thus, represent major limitations.…”
Section: Discussionmentioning
confidence: 99%